Parental history of childhood maltreatment and child average RSA shape parent-child RSA synchrony - Fuchs, Anna; Lunkenheimer, Erika; Brown, Kayla (Developmental psychobiology, 2021)
We examined whether dynamic parent-child RSA synchrony varied by individual differences in child average RSA and parental history of childhood maltreatment (CM), which has been linked to parental behavioral and physiological dysregulation. We also examined whether RSA synchrony was curvilinear, reflecting homeostatic regulation. Synchrony was defined as the dynamic association between parent and child RSA reactivity (change relative to their own mean) within epoch across a challenging task. Eighty-three mother-preschooler and 61 father-preschooler dyads participated. State-trait modeling showed that RSA synchrony was curvilinear such that significant relations were only found at lower and higher child reactivity. Children's higher task average RSA predicted maternal RSA augmentation and lower task average RSA predicted maternal RSA withdrawal, regardless of whether child reactivity in the moment was low or high, suggesting individual differences in child regulatory capacity were associated with dynamic maternal reactivity. When maternal CM history and child average RSA were both higher, mothers showed RSA augmentation. Father-child synchrony was not moderated by child average RSA but greater paternal CM history predicted fathers’ greater RSA withdrawal regardless of whether child RSA reactivity was low or high. Findings offer novel insights into the nature and meaning of RSA synchrony with parents at risk.
Gesehen am 28.11.2022